An integrated marketing communications campaign for Belo SunExpert - De Silva, Domini Zer Ann M. (Animo Repository, 2016)
According to Euromonitor International, CAGR of Sun Care category is anticipated to increase in its current value by 9% reaches Php 414 million in 2014. Sun care is expected to post a constant value CAGR of 5% by the end of 2019 with total value sales of Php 526 million. Nivea Sun of Beirsdorf Philippines is the market leader with a value share of 47% in 2014. As they have the largest product line to offer, diversity for the broad market. Multi-international companies such as Nivea Sun outperformed domestic players in the mentioned category as the wider range of products are enabling them to cater to a broader consumer segment. Domestic sun care player like Belo SunExpert has thoroughly been evolving in the sun care category. The continuous efforts have been taken by the brand to remain competitive in the market. To create brand equity, this campaign intends to extend product usage and to express how important applying sunscreen daily. The campaign use significant media channels that can directly communicate towards the target market, with a series of sub-campaigns that are promotional driven: Skin Squad (#SquadRules, #TravelSquad and #BestSquadStory).